Comparison of potency of inhaled beclomethasone and budesonide in New Zealand: retrospective study of computerised general practice records - Pethica, B D (British Medical Journal, 1998)
Objective To determine whether inhaled budesonide and beclomethasone are equipotent in the treatment of asthma in primary care. Design Retrospective study of computerised clinical records from 28 general practices in New Zealand. Subjects 5930 patients who received 16 725 prescriptions for inhaled budesonide or beclomethasone from 1 July 1994 to 30 June 1995. Setting General practices on the database of the Royal New Zealand College of General Practitioners Research Unit. Linked information from secondary care was available for a subset of the practices. Main outcome measure Mean prescribed daily inhaled corticosteroid dose. Results The daily prescribed dose was higher for patients receiving inhaled budesonide (mean 979 μg) than beclomethasone (mean 635 μg), a difference of 344 μg (95% confidence interval 313 to 376 μg). This difference was consistent in all age bands and with different types of inhalation device. Evidence of systematic prescribing of higher doses of budesonide to patients with more severe asthma was not found. Conclusions In primary care in New Zealand evidence suggests that budesonide is less potent than beclomethasone. Consideration of validated, established, and other possible markers of asthma severity did not support confounding by severity as a reason for the higher prescribed doses of budesonide. Pending further epidemiological evaluation, international asthma guidelines may need to be modified on the equivalence of inhaled corticosteroid doses. Furthermore, the comparative potency of newly developed inhaled steroids in clinical trials will need to be confirmed in appropriately designed epidemiological studies based in general practice.